The Influence of the Cooperative Script Method on Interest in Learning History - Muhammad Sopyan; Jamil Jamil; Aprisa Amping (Edumaspul: Jurnal Pendidikan, 2024)
This research aims to determine the influence and how big it is the significance of the influence of the cooperative script learning method on interest study student on eye lesson history in Senior High School 1 Linggang Confused. This approach uses a quantitative approach with experimental methods. The research design used was a posttest – only control design. The sample in there are two classes, namely the experimental class (XI IPS 1) and the control class (XI IPS 2). Data collection uses a questionnaire. Data analysis techniques used is regression with help SPSS 25. The results of hypothesis testing research were carried out based on coefficient data obtained mark significance as big as 0,000 from data the significance 0,000 <0.05 then H0 is rejected. Because H0 is rejected, Ha is accepted, so there is influence connection between method learning cooperative scripts to students' interest in learning, the magnitude of the coefficients for variables X and Y in the experimental class is 0.768 so that in categorize level correlation strong that is on range 0.6 – 0.799. This proves that students need more learning method more creative and innovative in helping teachers deliver material learning in the classroom. And the cooperative script learning method can used in the process learning history in class.